The Effect Of Service Quality On Public Satisfaction - Yusuf Yusuf; Nasrul Nasrul; Wahyuniati Hamid; Wa Ode Yusri (Cita konsultindo, 2023)
Public satisfaction can result from successful communication. Since frequent and good communication will lead to better public happiness, effective communication will help people to learn more and understand the importance of public satisfaction in an organization. This study aims to determine the effect of service quality on community satisfaction in the Tongkuno District Office, Muna Regency. A total of 75 residents of the Tongkuno sub-district who have accessed community services at the Tongkuno sub-district office participated in this study. This study uses survey and questionnaire methods that have been evaluated for reliability and validity. Multiple regression was used to analyze the data, and it was found that community satisfaction was significantly influenced by service quality, which included physical evidence (X1), empathy (X2), reliability (X3), responsiveness (X4), and assurance (X5). In the partial analysis it was found that physical evidence (X1) had a positive but not significant effect on community satisfaction, while reliability (X3), responsiveness (X4), assurance (X5), and empathy (X2) all had a positive and significant effect